Analisis Kekuatan Kolom Beton Bertulang Berdasarkan Diagram Interaksi Kolom - Indra Dody Kurniawan Manguki'; Jonie Tanijaya; Olan Jujun Sanggaria (Paulus Civil Engineering Journal, 2021)
The column interaction diagram is a boundary area graph showing the various combinations of axial loads and moments that the column can safely hold. The benefit of a column interaction diagram provides an overview of the strength of the column in question. This study aims to analyze rectangular and circular columns using column interaction diagrams and then compare the strength of the columns in withstanding a combination of axial loads and bending moments with the same area. In this study, square and circular columns have the same number of reinforcement, diameter of reinforcement, steel strength, concrete quality, and cross-sectional area. The column is reviewed based on five conditions, namely pure axial load conditions, pure bending moment, and three failure conditions. Based on the five conditions that occurred, a column interaction diagram was created by using Microsoft Excel. Results of the analysis show that in the same area, the square column is stronger in withstanding the bending moment (Mu) of the circular column by 0.015 - 0.61%, while the circular column is stronger in resisting the axial force (Pu) of the square column by 1,9 - 4.4%.